Different cooking styles enhance antioxidant properties and carotenoids of biofortified pumpkin (Cucurbita moschata Duch) genotypes - Moreira, Lara de Azevedo Sarmet; Jaeger de Carvalho, Lucia Maria; Cardoso, Flávio da Silva e Souza Neves; Dellamora Ortiz, Gisela Maria; Finco, Fernanda Dias Bartolomeu Abadio; Viana de Carvalho, José Luiz (FapUNIFESP, 2020)
Biofortification is an important technique where the nutritional quality of food crops is enriched through the increase of nutrient content. Provitamin A deficiency is still a public health concern mainly in developing countries. Since beta-carotene is a vitamin A precursor, the increase of this compound in foods through biofortification is a manner to reach people under hidden hunger condition. This work aimed to evaluate the effect of different cooking styles on carotenoids content and antioxidant activity of two different genotypes of biofortified Cucurbita moschata. In the present study, biofortified pumpkins submitted to different cooking conditions were assessed for antioxidant activity by ABTS, DPPH, β-carotene/linoleic acid systems and have polyphenols and carotenoids content compared. The cooking style affected the antioxidant activity. Pumpkins from genotype 1 showed high levels of carotenoids, α-carotene and all-E-β-carotene compared to samples from genotype 2. There was an increase of all carotenoids in both cooked pumpkins, and steam cooking showed the highest retention percentages. Steam cooking presented a higher percentage of carotenoid retention. Pumpkin consumption in developing countries, especially in the Northeast Brazil may be promoted to combat vitamin A deficiency.